Respuestas

  • Usuario de Brainly
2013-03-12T19:48:28+01:00

............x + 2.........4x

x + ----------- = ----------

.............6...............3

 

6x + x + 2...............4x

----------------- = ---------

......6......................3

 

(7x + 2)*3 = 4x * 6

21x + 6 = 24x

6 = 24x - 21x

6 = 3x

6/3 =x 

2 = x

 

 

x -1 ...........x +1

--------+ ---------- = x + 2

...2............3

 

3(x-1) + 2(x +1)

----------------------= (x +2)

............6

 

3x - 3 + 2x + 2 = 6x + 12

5x - 1 = 6x + 12

- 1 - 12 = 6x - 5x

- 13 = x

 

 

x -3 ...............x-5 .........x-1

--------- - ----------- = ------------

...4..............6...................9

 

6(x - 3) - 4(x - 5)........(x -1)

---------------------- = -----------

.............24.....................9

 

6x - 18 - 4x + 20..........(x - 1)

----------------------- = -------------

.............24.........................9

 

(2x + 2) . 9 = (x -1) .24

 

18x + 18 = 24x - 24

18 + 24 =  24x - 18x

42 = 6x

42/6 = x

7 = x

 

4x +1 ...........4x +1 ..........2x - 1

---------- - ------------- = ---------------

....3..................3...............5

 

0.............2x - 1

----- = --------------

3 ...............5

 

0 = (2x - 1) . 3

0 = 6x - 3

3 = 6x

3/6 = x

1/2 = x

 

 

3x+2............x - 2.................4x - 3

---------- - ----------- = 1 -  ----------

.......5............35.........................7

 

7(3x+2) - (x - 2).............7 - (4x - 3)

----------------------- =-----------------------

.................35.........................7

 

(21x + 14 - x + 2)7 = (7 - 4x + 3)35

(20x + 16) 7 = (10 - 4x) 35

140x + 112 = 350 - 140x

140x + 140x = 350 - 112

280x = 238

x = 238/280

x = 17/20

 

espero que te sirva, salu2!!!